Pengembangan Asesmen Formatif Terintegrasi Karakter Nilai Islam Berbasis Wordwall - Sari, Dewi; agustina, lady (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
This study aims to develop a formative assessment based on the Wordwall website, integrated with Islamic character values, as an interactive learning medium. The assessment not only measures students' cognitive understanding but also instills values of honesty, responsibility, and discipline. The researcher employed the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The resulting interactive assessment was implemented with 32 tenth-grade students of Class X F at SMA Muhammadiyah 3 Jember and validated by experts. The validation results indicated a "Highly Feasible" category, with a score of 90% from the content expert and 86% from the media expert. Additionally, 90% of students gave positive responses, indicating that the assessment is "Highly Engaging" as a medium for formative assessment.